Effects of improved on-farm crop storage on DNA methylation of mothers and their infants: evidence from a randomized controlled trial in Kenya - Heike Eichenauer; Susanne Fischer; Elena Gardini; Simon Onsongo; Ulrike Ehlert (Clinical Epigenetics, 2024)
Abstract Background Stress during pregnancy can lead to adverse maternal and infant health outcomes through epigenetic changes in the hypothalamic–pituitary–adrenal axis. Among farmers in low-income countries, one important stressor is food insecurity, which can be reduced using hermetic storage bags. This study aimed to determine, for the first time, whether a hermetic storage bag intervention during pregnancy positively affects maternal and infant DNA methylation of the hypothalamic–pituitary–adrenal axis-related genes FKBP5 and NR3C1. We further analyzed whether anthropometrics, stress, and mental health were associated with DNA methylation. Methods This study was part of a larger matched-pair randomized controlled trial focusing on the impact of improved on-farm storage on food security, poverty, and net income of smallholder farming households. A total of N = 149 mothers were recruited by telephone and invited to attend a study appointment at health facilities in Kakamega County, Western Kenya, with their infants in April or May 2021. During the appointment, anthropometric measurements were taken, questionnaires on stress and mental health were administered, and saliva samples were collected. Logistic and multiple linear regression were used to examine the effect of the intervention and related measures on DNA methylation. Results Mothers in the intervention group showed higher mean NR3C1 methylation levels than those in the control group, corrected for multiple testing. Maternal postpartum body mass index was positively associated with infant NR3C1 CpG3 DNA methylation. The more stressful life events a mother had experienced in the previous 12 months (including during pregnancy), the lower her FKBP5 CpG3 methylation levels. Conclusions Food insecurity and stressful life events during pregnancy seem to exert significant effects on maternal DNA methylation. While these stressors did not appear to impact infant DNA methylation in the present study, maternal postpartum body mass index was significantly related to infant methylation. These findings suggest that while infants may be protected from excessive maternal glucocorticoids by placental barrier activity, maternal metabolic status is still reflected in their epigenetic make-up. Trial registration This study was part of a larger matched-pair randomized controlled trial on the impact of improved on-farm crop storage on welfare, nutrition, and human health. Registration can be found in the American Economic Association (AEA) RCT Registry, RCT ID: AEARCTR-0005845.